2009
DOI: 10.1261/rna.1278109
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the seals: Efficient mRNA detection from human archival paraffin-embedded tissue

Abstract: During our study on HOXA13, HOXD12, and HOXD13 mRNA expression in human adult and embryonic tissues, we were confronted with the fact that, within our specimen collection, as in other University Departments in Europe, <20% of all samples yielded reliable labeling, while most samples were resistant to hybridization by standard protocols due to over-fixation. Fixation is essential for specimen stability, especially when samples are stored at room temperature and used for histology, and people tend to be more wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Furthermore, we were unable to confirm the role of differentiation and cell-cycle regulatory proteins, such as Bcl-2, P16 and P53, as well as CD44, as prognostic factors, similar to previous studies (8,(21)(22)(23)(24). The reasons may be different antibodies, antigen retrieval or inter-observer variations of the immunohistochemical staining (10,11,15).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, we were unable to confirm the role of differentiation and cell-cycle regulatory proteins, such as Bcl-2, P16 and P53, as well as CD44, as prognostic factors, similar to previous studies (8,(21)(22)(23)(24). The reasons may be different antibodies, antigen retrieval or inter-observer variations of the immunohistochemical staining (10,11,15).…”
Section: Discussioncontrasting
confidence: 54%
“…The general characteristics of the investigated GISTs are summarized in Table I. The range of fixation time for the obtained specimens was determined between 12 and 24 h in 4% phosphate-buffered saline-formalin solution to avoid false-positive or -negative immunohistochemical staining patterns due to under-or over-fixation (10,11).…”
Section: Methodsmentioning
confidence: 99%
“…7B). It is noteworthy that the expression of HOX genes was suppressed in close vicinity to rectal cancer samples (Illig et al, 2009), thereby outlining the difference between CDX2‐positive tumor from healthy HOX ‐gene‐positive tissue by a thin layer of cells that were negative for both HOX and CDX2. In contrast, other studies in human rectal tissues reported the lack of HOXD13 expression in normal tissue but an increase in neoplastic rectal tissue (Cantile et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For a better understanding of the processes involved in the development of the human hindgut, we collected specimens covering the age of developmental week 6 to 12. We recently developed a reliable method to investigate the expression of mRNAs in newly collected as well as archival samples (Illig et al, 2009, 2010). Applying this method, we present data demonstrating a clearly restricted temporal and spatial expression pattern of nine HOX gene members of the posterior clusters in human hindgut development and in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…The range of fixation time of the obtained specimens was between 12 and 24 h in 4% phosphate-buffered saline solution to avoid false-positive or -negative immunohistochemical staining patterns due to under- or over-fixation (14,15). …”
Section: Methodsmentioning
confidence: 99%